2016
DOI: 10.14202/vetworld.2016.699-704
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a recombinant human follicle stimulating hormone on the ovarian follicles, peripheral progesterone, estradiol-17β, and pregnancy rate of dairy cows

Abstract: Aims:This study aimed at elucidating the effects of recombinant human follicle stimulating hormone (r-hFSH) on the ovarian follicular dynamics, progesterone, estradiol-17β profiles, and pregnancy of dairy cows.Materials and Methods:Three groups (G, n=5 cows) of multiparous dairy cows were used. G1 (C) control cows were given controlled internal drug release (CIDR) and prostaglandin F2α; G2 (L) cows were given low dose (525 IU and G3 (H) cows were given high dose (1800 IU) of r-hFSH on twice daily basis at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hudson et al [23] indicated that exogenous FSH increased ovulation rates and pregnancy in Booroola ewes after hypothalamic-pituitary disconnection or after treatment with a gonadotropin-releasing hormone (GnRH) agonist. In a study on dairy cows, Ali and Zeitoun [24] reported that injection of 525 IU rh-FSH increased pregnancy rate from 60% in control to 100%, however, the injection of overdose (1800 IU) suppressed the ovulation and conception. In a study on Awassi sheep, the researchers found that the administration of a recombinant FSH, 24 h before the second PGF2α injection led to an increase in twin pregnancy rate [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hudson et al [23] indicated that exogenous FSH increased ovulation rates and pregnancy in Booroola ewes after hypothalamic-pituitary disconnection or after treatment with a gonadotropin-releasing hormone (GnRH) agonist. In a study on dairy cows, Ali and Zeitoun [24] reported that injection of 525 IU rh-FSH increased pregnancy rate from 60% in control to 100%, however, the injection of overdose (1800 IU) suppressed the ovulation and conception. In a study on Awassi sheep, the researchers found that the administration of a recombinant FSH, 24 h before the second PGF2α injection led to an increase in twin pregnancy rate [7].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low heritability of reproductive traits in animals, the need for non-genetic avenues for maximizing the productivity of local sheep became a necessity to meet the increased demand. Recent protocols for induction of twinning in single-bearing animals have increased the prolificacy of ewes (3) and cows (4). Earlier, Aköz et al (5) obtained high multiplelamb rates (69.2%) in Akkaraman crossbred ewes when they administered 700 IU rather than 300 or 500 IU of equine chorionic gonadotropin (eCG).…”
Section: Introductionmentioning
confidence: 99%